Investigations of Aluminium Metal Matrix Composite Process Parameters through Optimization using Taguchi’s Analysis - Ranjan Kumar Gupta; Amit Kumar Mandape (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Increasing fuel price created for weight reduction of products in automotive and aerospace industries. Requirement of better mechanical properties, quality, improved wear resistance, lower coefficient of thermal expansion leads to the development of aluminum composites of lighter weight. Silicon carbide proves to be the better reinforcement to the base metal because of its improved strength, hardness and chemical resistivity even at higher temperatures. Aluminium Metal matrix composites can be prepared by liquid state for industrial applications. In liquid state production method, stir casting process is generally preferred to its simplicity, flexibility and applicability to large quantity of production. It is also preferred due to the lesser production cost. The properties of the aluminium metal matrix composites are greatly influenced by the process parameters of the production methods. In this research work, stir casting method for preparing composites consisting of aluminium alloy and reinforcement of 10 % by weight proportion of silicon carbide. Experimental investigations are carried to optimize the process parameters of the production methods for the improvement of properties such as sliding wear resistance, compressive strength, abrasive wear and coefficient of thermal expansion of aluminum metal matrix composite. Taguchi’s experimental design is adopted for experimental conditions. In stir casting process, Taguchi’s analysis on process parameters shows that process temperature is significant parameter on compression strength, sliding wear resistance, abrasive wear resistance and coefficient of thermal expansion. The other process parameters such as stirring speed and stirring time are found to be insignificant from ANOVA for the above mentioned properties.
Keywords: Aluminium Metal Matrix; Stir Casting Process; Wears Resistance; Strength; Taguchi’s Analysis